PENGARUH KEPUASAN KERJA DAN PENGEMBANGAN KARIR TERHADAP JOB HOPPING INTENTION PADA KARYAWAN GENERASI MILENIAL DI KOTA PALEMBANG PADA INDUSTRI MAKANAN RINGAN - Kusuma, Noviyanti; Ratnasari, Agatha Septianna (Forum Bisnis Kewirausahaan, 2024)
This research aims to determine the negative influence of job satisfaction and career development on job hopping intention among millennial generation employees in Palembang city in the snack industry. The data used is primary data secondary data. The population in this research is millennial generation employees in the city of Palembang. The sample collection technique used was purposive sampling. Hypothesis testing was carried out by testing t count and F count. The results of the research show that there is a negative influence on job satisfaction and career development on job hopping intention among millennial generation employees in Palembang city in the snack industry. Keywords: Job Satisfaction, Career Development, Job Hopping Intention